Effects of dam construction on the reproduction of the Yellow River carp (Cyprinus carpio) in lower reaches of the Yellow River, China - Ruan, Qiongyao; Li, Wenda; Zhang, Shanghong; Tang, Caihong; Hou, Jun (Frontiers in Environmental Science, 2023)
The construction of dams changes the natural flow of rivers, affects the integrity of river ecosystems, and causes a series of ecological and environmental problems, such as habitat fragmentation and reduction in fish resources. This study took a section of the Yellow River in China from the Xiaolangdi Dam to Gaocun as the research area. The Yellow River carp (Cyprinus carpio) was selected as an indicator species for its economic value. A habitat suitability model for the Yellow River carp coupled with a one-dimensional hydrodynamic model was built. It was used to simulate dynamic changes in the reproductive habitat suitability of the Yellow River carp before and after the construction of the Xiaolangdi Dam. We demonstrated the spatial distribution of the carp’s spawning reaches before and after the Xiaolangdi Dam construction and investigated its influence on the spawning activity and larval development of the species accordingly. The results apparently showed that the construction and operation of the Xiaolangdi Dam delayed the breeding time of the Yellow River carp and decreased its quality by 5.28%. In particular, the larval fish development was greatly affected by the dam, with the quality being reduced by 8.95%. Furthermore, the habitat suitability of the spawning reaches slightly decreased as the extent of spawning reaches decreased by 16.23%, and several spawning reaches were lost entirely. This study shed light on the response of the Yellow River carp to hydrological and physical changes in the period 1980–1990 before the construction of the Xiaolangdi Dam and 2006–2018 after the construction. Thus, it is a valuable reference for the ecological scheduling of discharges of the Xiaolangdi Dam.